Optimization of capacity utilization using time-driven activity-based costing for library system - Mohd Yazid, Abu; S N A M, Zaini (IOP Publishing, 2021)
Library system encourages and offers a number of opportunities to access the resource of desired information. Nonetheless, there is a problem in the current practice in library system which do not explain the relation between supplied resources and practical capacity. To view it in the form of unused capacity, they should establish capacity cost rates (CCR). In efforts to support in reducing costs and divert the workforce for far more important activities, unused capacity analysis is ultimately critical in forecast planning. This work aims to develop a new costing system for optimization of capacity utilization in library system. Time driven activity-based costing (TDABC) was applied in UMP library. While TDABC can enhance costs control for a range of library processes, it only focuses on acquisition and cataloging processes in this work. The analysis of data is carried out through four steps which are process mapping, time equation, CCR and forecast analysis. In this work, the total unused capacity at the acquisition center, in both local and overseas are 2,700,32 and 7,199,83 minutes. While in cataloging center, the total unused capacity are -393.05 and 5,468.35 minutes in local and oversea material respectively.